An in silico–in vitro pipeline for drug cardiotoxicity screening identifies ionic pro‐arrhythmia mechanisms. (24th July 2022) - Clark, Alexander P.; Wei, Siyu; Kalola, Darshan; Krogh‐Madsen, Trine; Christini, David J.
Abstract : Background and Purpose: Before advancing to clinical trials, new drugs are screened for their pro‐arrhythmic potential using a method that is overly conservative and provides limited mechanistic insight. The shortcomings of this approach can lead to the mis‐classification of beneficial drugs as pro‐arrhythmic. Experimental Approach: An in silico – in vitro pipeline was developed to circumvent these shortcomings. A computational human induced pluripotent stem cell‐derived cardiomyocyte (iPSC‐CM) model was used as part of a genetic algorithm to design experiments, specifically electrophysiological voltage clamp (VC) protocols, to identify which of several cardiac ion channels were blocked during in vitro drug studies. Such VC data, along with dynamically clamped action potentials (AP), were acquired from iPSC‐CMs before and after treatment with a control solution or a low‐ (verapamil), intermediate‐ (cisapride or quinine) or high‐risk (quinidine) drug. Key Results: Significant AP prolongation (a pro‐arrhythmia marker) was seen in response to quinidine and quinine. The VC protocol identified block of IKr (a source of arrhythmias) by all strong IKr blockers, including cisapride, quinidine and quinine. The protocol also detected block of ICaL by verapamil and Ito by quinidine. Further demonstrating the power of the approach, the VC data uncovered a previously unidentified If block by quinine, which was confirmed with experiments using a HEK‐293 expression system and automated patch‐clamp. Conclusion and Implications: We developed an in silico – in vitro pipeline that simultaneously identifies pro‐arrhythmia risk and mechanism of ion channel‐blocking drugs. The approach offers a new tool for evaluating cardiotoxicity during preclinical drug screening. Abstract :